2020
DOI: 10.1021/jacs.0c00553
|View full text |Cite
|
Sign up to set email alerts
|

Rapid, Scalable Construction of Highly Crystalline Acylhydrazone Two-Dimensional Covalent Organic Frameworks via Dipole-Induced Antiparallel Stacking

Abstract: Covalent organic frameworks are an emerging class of porous crystalline organic materials that can be designed and synthesized from the bottom up. Despite progress made in synthesizing COFs of diverse topologies, the synthesis methods are often tedious and unscalable, hampering practical applications. Herein, we demonstrate a scalable, robust method of producing highly crystalline acylhydrazone two-dimensional (2D) COFs with diversified structures (six examples) under open and stirred conditions, with growth t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
110
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(115 citation statements)
references
References 56 publications
5
110
0
Order By: Relevance
“…Smart materials (also referred to intelligent or stimuli‐responsive materials) can undergo reversible changes by external stimuli, such as temperature, light, pH, gases, chemical compounds, or moisture, have attracted intense attention in many fields as diverse as sensors, [15] actuators, [16] artificial muscles, [17] and information storage [18] . Covalent organic frameworks (COFs) [19–21] have emerged as a new class of smart materials and exhibited diverse, intelligent applications such as actuating, [22] drug delivery, [23, 24] and sensing [25] due to their high crystallinity and porosity, [26] defined pore environment, [27] high emission efficiency, [28] and extraordinary chemical stability [29, 30] . Moreover, COFs can be readily predesigned and post‐synthetically modified.…”
Section: Introductionmentioning
confidence: 99%
“…Smart materials (also referred to intelligent or stimuli‐responsive materials) can undergo reversible changes by external stimuli, such as temperature, light, pH, gases, chemical compounds, or moisture, have attracted intense attention in many fields as diverse as sensors, [15] actuators, [16] artificial muscles, [17] and information storage [18] . Covalent organic frameworks (COFs) [19–21] have emerged as a new class of smart materials and exhibited diverse, intelligent applications such as actuating, [22] drug delivery, [23, 24] and sensing [25] due to their high crystallinity and porosity, [26] defined pore environment, [27] high emission efficiency, [28] and extraordinary chemical stability [29, 30] . Moreover, COFs can be readily predesigned and post‐synthetically modified.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 However, interlayer hydrogen bonding in COFs is much rarer. There are only a few examples of hydrazone 17,18 or urea 12 containing COFs where interlayer hydrogen bonding is observed or predicted, reported in literature. Several COFs have been reported that have interlayer C-H⋯O, and C-H⋯N hydrogen bonding through sidechain interactions, 13,14,19 however, more canonical N-H⋯O hydrogen bonding interactions similar to those found between amide groups found in Nature, or in synthetic polymers such as Kevlar or Nylon, are much rarer.…”
mentioning
confidence: 99%
“…To give the readers a better understanding of this promising approach, detailed examples of COF syntheses in an atmospheric solution are summarized in Table 1. [120][121][122][123][124][125][126][127][128][129][130][131][132][133][134]…”
Section: Atmospheric Solution Synthesismentioning
confidence: 99%